Perang salib: latar belakang, periodisasi, dan implikasinya terhadap peradaban modern - Mukharomah, Awwalina (Maliki Interdisciplinary Journal, 2025)
The Crusades that took place between 1095 AD and 1291 AD were long-term wars involving Muslims and European Christians. This war is driven by many factors, including religious, economic, and political factors. The course of the war is divided into 3 main periods, each with its main actors, where the first period was won by the Franks, the second by the Muslims, and the same for the third period. The implications resulting from the outbreak of the Crusades have influenced subsequent human civilization, especially in modern times. The development of science, economy, and military shaped the world's civilization after the occurrence of this war. Nevertheless, the war also resulted in a form of regression for Islamic civilization that lasted for an extended period.